2020
DOI: 10.1111/liv.14562
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is associated with suspected non‐alcoholic fatty liver disease and all‐cause mortality in the general population

Abstract: Background & Aims Non‐alcoholic fatty liver disease (NAFLD) is characterized by excessive lipid accumulation, inflammation and an imbalanced redox homeostasis. We hypothesized that systemic free thiol levels, as a proxy of systemic oxidative stress, are associated with NAFLD. Methods Protein‐adjusted serum free thiol concentrations were determined in participants from the Prevention of Renal and Vascular End‐Stage Disease (PREVEND) cohort study (n = 5562). Suspected NAFLD was defined by the Fatty Liver Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
(62 reference statements)
6
20
0
Order By: Relevance
“…In the present study, we observed independent associations between serum free thiols and systolic blood pressure, hs-CRP and eGFR among premenopausal females, and with age, BMI, eGFR, and hemoglobin levels among postmenopausal females. These associations corroborate the findings of previous studies that examined serum free thiols in both healthy and diseased population cohorts ( 8 , 12 , 13 , 37 , 38 ). All these associations reflect a strong association between reduced systemic oxidative stress (i.e., lower levels of serum free thiols) and a favorable cardiovascular risk profile (e.g., lower age, BMI, blood pressure and hs-CRP, and higher eGFR and hemoglobin levels).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we observed independent associations between serum free thiols and systolic blood pressure, hs-CRP and eGFR among premenopausal females, and with age, BMI, eGFR, and hemoglobin levels among postmenopausal females. These associations corroborate the findings of previous studies that examined serum free thiols in both healthy and diseased population cohorts ( 8 , 12 , 13 , 37 , 38 ). All these associations reflect a strong association between reduced systemic oxidative stress (i.e., lower levels of serum free thiols) and a favorable cardiovascular risk profile (e.g., lower age, BMI, blood pressure and hs-CRP, and higher eGFR and hemoglobin levels).…”
Section: Discussionsupporting
confidence: 91%
“…It was well documented that the four parameters of free thiol, carbonyl, AGE, and hcy are closely related to various diseases such as diabetes mellitus, cardiovascular diseases, adiposity, and Alzheimer's disease [10,23,29,[36][37][38]. We discovered that longevity is intimately related to these four major parameters, based on which we defined the status of exogenous rMSA as "young and undamaged".…”
Section: Discussionmentioning
confidence: 97%
“…NAFLD patients also show increased levels of peroxidised lipids, such as malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE), which are often used as biomarkers of lipid peroxidation in clinical practice [9]. Moreover, a recent report suggests that reduced levels of free thiol plasma levels can be considered as a global marker of the systemic load of reactive species and can be used as a biomarker for NAFLD [39].…”
Section: Oxidative Stress Biomarkers In Nafld Patientsmentioning
confidence: 99%